Exploration of Hermite–Hadamard-Type Integral Inequalities for Twice Differentiable h-Convex Functions - Miguel Vivas-Cortez; Muhammad Samraiz; Muhammad Tanveer Ghaffar; Saima Naheed; Gauhar Rahman; Yasser Elmasry (Fractal and Fractional, 2023)
The significance of fractional calculus cannot be underestimated, as it plays a crucial role in the theory of inequalities. In this paper, we study a new class of mean-type inequalities by incorporating Riemann-type fractional integrals. By doing so, we discover a novel set of such inequalities and analyze them using different mathematical identities. This particular class of inequalities is introduced by employing a generalized convexity concept. To validate our work, we create visual graphs and a table of values using specific functions to represent the inequalities. This approach allows us to demonstrate the validity of our findings and further solidify our conclusions. Moreover, we find that some previously published results emerge as special consequences of our main findings. This research serves as a catalyst for future investigations, encouraging researchers to explore more comprehensive outcomes by using generalized fractional operators and expanding the concept of convexity.